2004
DOI: 10.1021/jf0497556
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Liquid Chromatography−Tandem Mass Spectrometry Method for Quantification of the Plant Lignans Secoisolariciresinol, Matairesinol, Lariciresinol, and Pinoresinol in Foods

Abstract: A liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was developed for the quantification of the four major enterolignan precursors [secoisolariciresinol, matairesinol, lariciresinol, and pinoresinol] in foods. The method consists of alkaline methanolic extraction, followed by enzymatic hydrolysis using Helix pomatia (H. pomatia) beta-glucuronidase/sulfatase. H. pomatia was selected from several enzymes based on its ability to hydrolyze isolated lignan glucosides. After ether extraction samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
94
3
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 34 publications
6
94
3
1
Order By: Relevance
“…Microwave-assisted extraction of SDG in flaxseed has also been described recently allowing a gain of time but no marked improvements of yield were obtained (Beejmohun et al, 2007;Nemes & Orsat, in press;Zhang & Xu, 2007; Table 1). Finally, various enzymes such as b-glucuronidase or sulfatase have been used in flax lignan release but without marked improvement of yield (Mazur et al, 1996;Milder et al, 2004;Obermeyer et al, 1995; see Table 1). Kraushofer and Sontag (2002) reported the use of cellulase to release the aglycone form of SDG from flaxseed; however enzymatic parameters have not been optimised.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave-assisted extraction of SDG in flaxseed has also been described recently allowing a gain of time but no marked improvements of yield were obtained (Beejmohun et al, 2007;Nemes & Orsat, in press;Zhang & Xu, 2007; Table 1). Finally, various enzymes such as b-glucuronidase or sulfatase have been used in flax lignan release but without marked improvement of yield (Mazur et al, 1996;Milder et al, 2004;Obermeyer et al, 1995; see Table 1). Kraushofer and Sontag (2002) reported the use of cellulase to release the aglycone form of SDG from flaxseed; however enzymatic parameters have not been optimised.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, after enzymatic hydrolysis, the active ingredients may also dissolve more easily in the extraction medium (6,14). Previously, it was reported that the secoisolariciresinol diglucoside lignans and polyphenol aglycone of secoisolariciresinol from flaxseed are better extracted after enzymatic hydrolysis by glucuronidase, cellulase or sulfatase (24)(25)(26)(27). It was also observed by other researches (28)(29)(30) that enzymatic hydrolysis of polyphenol glycosides by Rhizopus oligosporusn beta-glucosidase (29,30) and commercial pectinases (28) can increase the total phenolic content and the antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
“…The method of direct acid hydrolysis by Liggins et al (2000) was chosen since the literature data showed this method to result in the highest amounts of flaxseed SECO (12 617 µg/g and 7400 µg/g) detected. When applying ethanol or methanol extraction prior to acid, alkaline, or enzymatic hydrolyses, the detected amounts were in the range of 1570-6994 μg/g for SECO and 600-900 μg/g for ANHSECO (Milder et al 2004;Peñalvo et al 2005;Thompson et al 2006;Smeds et al 2007;Krajčová et al 2009;Popova et al 2009). Altough the discrepancy between the results of different methods could be explained by the differences in the plant variety and growth conditions ( Johnsson et al 2000), the work comparing alkaline hydrolysis of dioxane/ethanol extracts with direct alkaline hydrolysis showed better recovery of SDG using direct hydrolysis (Eliasson et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, acid or alkaline hydrolysis or combinations of these with enzyme hydrolysis have been applied to obtain lignan aglycones (Table 1). For the identification and quantification of lignans from food, high performance liquid chromatography (HPLC) with diode array detection (DAD) (Meagher et al 1999;Johnsson et al 2000;Eliasson et al 2003;Zhang & Xu 2007), coulometric electrode array (CEA) detection system (Kraushofer & Sontag 2002;Schwartz & Sontag 2006), and MS/MS detectors (Milder et al 2004;Smeds et al 2007) or GC/MS (Mazur et al 1996;Meagher et al 1999;Liggins et al 2000;Sicilia et al 2003;Peñalvo et al 2005;Thompson et al 2006;Popova et al 2009) have been used. In Table 1, the overview is given of the methods developed for flaxseed lignan gas chromatography-mass spectrometry (GC/MS) analysis.…”
mentioning
confidence: 99%